The Relationship between Plasminogen Activator Inhibitors and the Severity of COVID-19 - Troeman, Kyna; Aman, Adi Koesoema; Nasution, Malayana Rahmita (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
The fibrinolysis process is assisted by plasminogen activators and inhibitors by converting plasminogen into plasmin, which later will promote the fibrinolysis process. Incomplete fibrinolysis increases the risk of thrombosis in patients with COVID-19. Plasminogen Activator Inhibitor (PAI-1) plays an important role as acute phase reactants to be used as a marker to assess the prognosis and mortality of COVID-19 patients. This study aimed to elaborate on whether fibrinolysis shutdown occurs in COVID-19 patients using PAI-1 as a marker of fibrinolysis. This was a cross-sectional analytical study from November 2022 to May 2023. This research consisted of a total of 39 patients with COVID-19, hospitalized at Haji Adam Malik General Hospital, Medan. PAI-test in COVID-19 patients was carried out with the ELISA method using Chemwell Analyzer. The severity of COVID-19 measured by clinical examination was divided into moderate, severe, and critical. The association between the two variables was subjected to a comparative test followed by a correlation test to explore the association between the two variables with an independent T-test. In this study, the median PAI-1 level was 1.77 ng/mL (0.71–11.49 ng/mL). The highest PAI-1 levels were observed in the critical severity group, followed by the severe and moderate group of 8.54 ng/mL (5.76–10.84), 2.45 ng/mL (0.71–11.49), and 1.29 ng/mL (0.73–3.77), respectively. There was a significant relationship between PAI-1 levels and the severity of COVID-19 patients (p=0.003). PAI-1 cut-off value of 1.89 ng/mL may predict the degree of COVID-19 severity with sensitivity of 88.9%, specificity of 90.5%, and accuracy of 89.7%. This study classified the severity of COVID-19 into two categories, which are moderate (n=21) and severe-critical (n=18) to obtain the AUC value of PAI-1. PAI-1 can be used to predict the severity of COVID-19 disease with a moderate level (AUC >70–80%). This phenomenon can be secondary to enhanced platelet aggregation, inflammation micro thrombosis, and impaired fibrinolysis. Fibrinolysis disorders lead to a fibrin buildup and increased levels of PAI-1 in the circulation.